Pengaruh Pelatihan, Budaya Organsiasi dan Pengawasan Terhadap Kinerja Pegawai - Numberi, George Mellis; Noch, Muhamad Yamin; Suratini, Suratini (Paradoks : Jurnal Ilmu Ekonomi, 2024)
This study is associative research aimed at analyzing, identifying, and explaining the influence of training, organizational culture, and supervision on civil servants' (ASN) performance in the General Bureau and Protocol of the Regional Secretary (SEKDA) of Papua Province. The data used in this study consisted of 69 respondents out of a total population of 276 civil servants, using the Simple Random Sampling probability sampling technique. The primary data source for this research was obtained by distributing questionnaires to all respondents. The statistical method used to test the hypotheses was multiple linear regression analysis using SPSS. Based on the results of partial and simultaneous testing, it was found that training, organizational culture, and supervision significantly influence the performance of civil servants in the General Bureau and Protocol of the SEKDA of Papua Province. This study not only highlights the dynamics within the General Bureau and Protocol of the SEKDA of Papua Province but also provides a deeper understanding of the factors influencing the performance of civil servants.